EFEKTIVITAS PREGNANCY BODY MASSAGE TERHADAP TINGKAT KECEMASAN IBU HAMIL TRIMESTER III - Evi fidiarti; Indah Puspitasari; Indah Risnawati (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2026)
Pregnancy in the third trimester is often accompanied by physical and psychological changes that can cause anxiety before delivery. Excessive anxiety can negatively impact the health of the mother and fetus. Non-pharmacological interventions such as Pregnancy Body Massage are known to be able to provide a relaxation effect, reduce stress hormones, and increase the comfort of pregnant women.This study aims to determine the effectiveness of Pregnancy Body Massage on the level of anxiety of pregnant women in the third trimester at PKU Muhammadiyah Gubug Hospital. This study used a quantitative design with a quasi experiment method and a pre-test and post-test without control group approach. The study population was all pregnant women in the third trimester who conducted examinations at PKU Muhammadiyah Gubug Hospital as many as 39 people, with a sample of 36 respondents taken using purposive sampling techniques. Anxiety level measurements were carried out using the Hamilton Anxiety Rating Scale (HARS) questionnaire before and after the Pregnancy Body Massage intervention. Data analysis using Wilcoxon test.The results of statistical analysis of the wilcoxon test obtained p value = 0.000. It can be concluded that there is an Effect of Pregnancy Body Massage on the Anxiety Level of Pregnant Women in the Third Trimester at PKU Muhammadiyah Gubug Hospital. There is an Effect of Pregnancy Body Massage on the Level of Anxiety of Pregnant Women in the Third Trimester at PKU Muhammadiyah Gubug Hospital